Shoot growth of woody trees and shrubs is predicted by maximum plant height and associated traits. (11th September 2017) - Gleason, Sean M.; Stephens, Andrea E. A.; Tozer, Wade C.; Blackman, Chris J.; Butler, Don W.; Chang, Yvonne; Cook, Alicia M.; Cooke, Julia; Laws, Claire A.; Rosell, Julieta A.; Stuart, Stephanie A.; Westoby, Mark
Abstract: The rate of elongation and thickening of individual branches (shoots) varies across plant species. This variation is important for the outcome of competition and other plant–plant interactions. Here, we compared rates of shoot growth across 44 species from tropical, warm temperate and cool temperate forests of eastern Australia. Shoot growth rate was found to correlate with a suite of traits including the potential height of the species, xylem‐specific conductivity, leaf size, leaf area per xylem cross‐section (LA/XA), twig diameter (at 40 cm length), wood density and modulus of elasticity. Within this suite of traits, maximum plant height was the clearest correlate of growth rates, explaining 50%–67% of the variation in growth overall ( p < .0001), and 23%–32% of the variation ( p < .05) in growth when holding the influence of the other traits constant. Structural equation models suggest that traits associated with "hydraulics, " "biomechanics" and the "leaf economics spectrum" represent three clearly separated axes of variation, with the hydraulic axis exhibiting the strongest alignment with height and largest independent contribution to growth (in the case of branch thickening). However, most of the capacity of these axes to predict growth was also associated with maximum height, presumably reflecting coordinated selection on multiple traits that together influence life histories. Growth rates were not strongly correlated with leaf nitrogen or leaf mass per unit leaf area. Correlations between growth and maximum height arose both across latitude (47%, p < .0001) and from within‐site differences between species (30%, p < .0001). Covariation between growth and maximum height was driven in part by variation in irradiance across sites as well as among canopy positions within sites (23%, p < .0001). A significant fraction of this shared variation was independent of irradiance (45%, p < .0001), reflecting intrinsic differences across species and sites. A plain language summary is available for this article. Abstract : Plain Language Summary